Biological and environmental exposure monitoring of volatile organic compounds among nail technicians in the Greater Boston area. (21st May 2019) - Ceballos, Diana M.; Craig, Jessica; Fu, Xianqiang; Jia, Chunrong; Chambers, David; Chu, MyDzung T.; Fernandez, Alai T.; Fruh, Victoria; Petropoulos, Zoe E.; Allen, Joseph G.; Vallarino, Jose; Thornburg, Lydia; et al.
Abstract: Nail technicians are exposed to volatile organic compounds (VOCs) from nail products, but no studies have previously measured VOC biomarkers for these workers. This study of 10 nail technicians aimed to identify VOCs in nail salons and explore relationships between air concentrations and biomarkers. Personal and area air samples were collected using thermal desorption tubes during a work shift and analyzed using gas chromatography/mass spectrometry (GC/MS) for 71 VOCs. Whole blood samples were collected pre‐shift and post‐shift, and analyzed using GC/MS for 43 VOCs. Ventilation rates were determined using continuous CO2 measurements. Predominant air VOC levels were ethyl methacrylate (median 240 µg/m 3 ), methyl methacrylate (median 205 µg/m 3 ), toluene (median 100 µg/m 3 ), and ethyl acetate (median 639 µg/m 3 ). Blood levels were significantly higher post‐shift than pre‐shift for toluene (median pre‐shift 0.158 µg/L and post‐shift 0.360 µg/L) and ethyl acetate (median pre‐shift <0.158 µg/L and post‐shift 0.510 µg/L); methacrylates were not measured in blood because of their instability. Based on VOCs measured in these seven nail salons, we estimated that emissions from Greater Boston area nail salons may contribute to ambient VOCs. Ventilation rates did not always meet the ASHRAE guideline for nail salons. There is a need for changes in nail product formulation and better ventilation to reduce VOC occupational exposures.